Managing conflict through communication - Cahn, Dudley D; Abigail, Ruth Anna (Boston : Pearson, 2014)
Managing Conflict Through Communication helps students approach conflict constructively and learn more positive conflict management and resolution skills. Narratives and case studies make the material accessible and engaging to a diverse student audience. Discussion questions and exercises throughout the text provide a basis for classroom discussion and practical applications of concepts
Introduction to the study of conflict communication -- Communication options in conflict -- Managing conflict from a theoretical perspective -- Responding to conflict : A practical guide to managing your own conflicts -- Managing violent tendencies -- Managing the conflict climate -- Managing face -- Managing stress and anger -- Managing conflict through forgiveness -- Managing win-lose conflicts through negotiation -- Managing others' disputes through mediation -- Managing conflict in the workplace -- Managing social conflict
Includes bibliographical references and index
Keywords: Conflict (Psychology); Interpersonal conflict; Conflict management